Status and Exploitation of 74 Un-Assessed Demersal Fish and Invertebrate Stocks in the Aegean Sea (Greece) Using Abundance and Resilience - Tsikliras, Athanassios C.; Touloumis, Konstantinos; Pardalou, Androniki; Adamidou, Angeliki; Keramidas, Ioannis; Orfanidis, Georgios A.; Dimarchopoulou, Donna; Koutrakis, Manos (Frontiers in Marine Science, 2021)
Stocks with low market value are rarely included in stock assessments because their catch records are generally lacking, thus adding to the already large number of un-assessed fisheries at a global scale. Τhis deficiency is more evident in the Mediterranean Sea where stock assessments are relatively fewer. A new method (AMSY) has been recently developed to assess stocks for which only abundance trends from scientific surveys are available. We used the AMSY method in the Aegean Sea to assess the status of 74 fish and invertebrate stocks (50 actinopterygians, 4 sharks, 5 rays, 12 cephalopods and 3 crustaceans) for which catch data are lacking; 20 of them have medium or high market value and are being targeted by fishing fleets, while the remaining 54 are either not targeted, but by-caught and often discarded, or are not exploited at all. Based on B/Bmsy results, 31 of the 54 non-targeted stocks (57%) were healthy with B/Bmsy values exceeding unity, whereas only 6 of the 20 targeted stocks (30%) were healthy. Of the 23 unhealthy non-targeted stocks, 12 had B/Bmsy values exceeding 0.75, compared to only 1 of the targeted stocks, whereas 10 non-targeted stocks (19%) and 10 targeted ones (50%) were outside safe biological limits (B < 0.5Bmsy). Cephalopods and crustaceans were generally in a better status compared to fishes. The results confirm that fishing does not only affect commercial stocks, but it may also affect by-catch stocks. In general, stocks that are targeted by fishing fleets are in a worse status in terms of biomass compared to those that are only occasionally collected as by-catch or those that inhabit environments that are not accessible to fishing fleets.